2004
DOI: 10.4319/lo.2004.49.4.0997
|View full text |Cite
|
Sign up to set email alerts
|

The demise of the marine cyanobacterium, Trichodesmium spp., via an autocatalyzed cell death pathway

Abstract: We present experimental laboratory evidence and field observations of an autocatalyzed, programmed cell death (PCD) pathway in the nitrogen-fixing cyanobacterium Trichodesmium spp., which forms massive blooms in the subtropical and tropical oceans. The PCD pathway was induced in response to phosphorus and iron starvation as well as high irradiance and oxidative stress. Transmission electron microscopy revealed morphological degradation of internal components including thylakoids, carboxysomes, and gas vesicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
298
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(323 citation statements)
references
References 31 publications
22
298
3
Order By: Relevance
“…These findings are in agreement with recent reports demonstrating that caspase activity is a common constituent not only in mammalian systems but in higher plants and lower algae as well (Korthout et al, 2000, Elbaz et al, 2002, Segovia et al, 2003. Our results, in conjunction with the recent caspase-like activity found in Trichodesmium (Berman-Frank et al, 2004), support the notion that PCD has an earlier evolutionary origin and broader significance than previously thought.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings are in agreement with recent reports demonstrating that caspase activity is a common constituent not only in mammalian systems but in higher plants and lower algae as well (Korthout et al, 2000, Elbaz et al, 2002, Segovia et al, 2003. Our results, in conjunction with the recent caspase-like activity found in Trichodesmium (Berman-Frank et al, 2004), support the notion that PCD has an earlier evolutionary origin and broader significance than previously thought.…”
Section: Discussionsupporting
confidence: 83%
“…This process is termed oxidative cell stress (Van Camp et al, 1998). Aside from what has been documented in Trichodesmium (Berman-Frank et al, 2004), the involvement of oxidative stress on PCD has not been previously shown in other cyanobacterium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…already by Lenes et al (2005) and Moutin et al (2005). This process could reduce growth rates, in a 483 way opposite to the nutrient increase effect described above, or induce mortality through a 484 "Programmed Cell Death" (PCD) pathway (Berman-Frank et al, 2004, 2007. Viral lysis (Ohki, 485 1999) and PCD, caused by other factors than nutrient depletion, as listed by Berman-Franck et al 486 (2004), are other possible processes.…”
Section: Decline Origin 476mentioning
confidence: 99%